Mitochondrial Mayhem: How cigarette smoke induces placental dysfunction through MMS19 degradation - Pei Zhou; Feng Jin; Shenshen Yao; Ben Sun; Ni Sun; Hongbo Guan; Xiaomei Liu (Ecotoxicology and Environmental Safety)
Cigarette smoke (CS) has detrimental effects on placental growth and embryo development, but the underlying mechanisms remain unclear. This study aims to investigate the impact of CS on trophoblast cell proliferation and regulated cell death (RCD) by examining its interference with iron-sulfur cluster (ISC) proteins and the CIA pathway. Exposure to CS disrupted the cytosolic ISC assembly (CIA) pathway, downregulated ISC proteins, and decreased ISC maturation in the placenta of rats exposed to passive smoking. Studies using HTR-8/Sneo cells demonstrated that cigarette smoke extract (CSE) inhibits trophoblast proliferation, activates autophagy, and induces apoptosis by impairing the CIA pathway and ISC proteins. Molecular docking analysis revealed that nicotine and nicotyrine bind to and promote the autophagic-dependent degradation of MMS19, a key component of the CIA complex. MMS19 KD led to the autophagic degradation of several ISC proteins involved in DNA damage repair and mitochondrial respiratory function, thereby inhibiting cell proliferation. Additionally, MMS19 deficiency resulted in mitochondrial fragmentation, ROS accumulation, and the induction of autosis and apoptosis. Transcriptome analysis indicated that dysregulation of the SMAD pathway mediates mitochondrial damage induced by MMS19 KD. Analysis of placental tissues from maternal smokers further confirmed the disruption of ISC proteins and the SMAD pathway. This study suggests that disruption of the CIA pathway and ISC proteins contributes to placental maldevelopment induced by CS. Targeting the MMS19-SMAD pathway may offer a potential strategy to mitigate adverse pregnancy outcomes caused by CS.